Visual perception development and its relationship with academic achievement among kindergarten children - Mohd Arshad, Nadiah; Shafiin, Nurul Syuhada; Mohd Jelani, Nurul Syazana; Ma'rof, Aini Marina (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
The main objectives of this study are to analyze the differences in visual perception between 4 years old and 6 years old children in a kindergarten in Selangor and to investigate the correlations between visual perception and academic achievement. This study is a between-subject design experiment in which the subjects were purposively selected and the test is conducted individually to each subjects with guidance and instruction from the researchers. Subjects consisted of 19 children aged four and six years old. The Kindergarten Readiness Test test was used to identify children’s visual cognitive perceptual development. The gathered quantitative data was analysed using IBM SPSS Statistics version 22. The academic achievement data of the children were supplied by the class teacher. Findings show that there are significant differences in visual perception between 4 years old and 6 years old children and there is a significant relationship between visual perception among 4 years old children and their academic scores but visual perception does not significantly correlate with 6 year old children’s academic attainment indicating that visual perceptual development plays an important role in academic achievement in the early years of kindergarten.